Scholastic profile of Argentine competitive tennis players - Maquirriain, J. (Medicine and Science in Tennis, 2006)
The objective of this survey was to obtain the scholastic profile of Argentine junior tennis players. We studied 51 junior competitive tennis players of both sexes (23 female; 28 male) with an average age of 15.19 years (range 13-18; sd 1.29). Players were asked to complete a mostly closed questionnaire, comprising 19 items regarding the amount of weekly training days, number of daily hours training, necessity of more hours of training, school attendance, parents´ level of education and expectation to continue a professional tennis career.